2009
DOI: 10.1002/jrs.2474
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of the short‐range disorder due to erbium doping in Pb0.8La0.2TiO3films

Abstract: We show the destruction of a displacement of Ti in the short-range structure by observing the disappearance of emission and Raman signals when the Er 3+ concentration exceeds 7 mol% in sol-gel-derived Pb 0.8 La 0.2 TiO 3 polycrystalline films. It is believed that there always exists disorder due to displacement of B ions in the skeleton of BO 6 in perovskite ABO 3 materials. This disorder due to the displacement of Ti ions breaks the center of symmetry to activate emission of rare-earth ions such as Er 3+ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Huang et al . demonstrated the destruction of a displacement of Ti in the short‐range structure of a film of Pb 0.8 La 0.2 TiO 3 by observing the disappearance of emission and Raman signals when the Er 3+ concentration exceeded 7 mol.% in sol–gel‐derived polycrystalline films . They found that symmetry breaking can be diminished by introducing more Er 3+ ions.…”
Section: Solid‐state Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al . demonstrated the destruction of a displacement of Ti in the short‐range structure of a film of Pb 0.8 La 0.2 TiO 3 by observing the disappearance of emission and Raman signals when the Er 3+ concentration exceeded 7 mol.% in sol–gel‐derived polycrystalline films . They found that symmetry breaking can be diminished by introducing more Er 3+ ions.…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…Huang et al demonstrated the destruction of a displacement of Ti in the short-range structure of a film of Pb 0.8 La 0.2 TiO 3 by observing the disappearance of emission and Raman signals when the Er 3+ concentration exceeded 7 mol.% in sol-gel-derived polycrystalline films. [204] They found that symmetry breaking can be diminished by introducing more Er 3+ ions. Rossella et al published the results of a systematic study performed by micro-Raman spectroscopy on pure anatase, pure rutile and mixed anatase-rutile TiO 2 thin films, deposited by radio frequency magnetron sputtering on quartz substrates, with different thicknesses.…”
Section: Glasses Ceramics and Disordered Materialsmentioning
confidence: 99%